Current station and trends in the development of pig breeding in Ukraine - Hurzhii, Nataliia; Reshetov, Serhii; Lyshnikova, Anastasiia (Management and Entrepreneurship: Trends of Development, 2022)
The article is devoted to the disclosure of the topic of pig farming in Ukraine, import and export of products, various statistical data on the products of countries with which Ukraine cooperates are presented. The topic of developing the potential of pig farming in general was developed. The topic of ASF and its consequences is revealed. Comments from various analysts are provided. Graphs, charts and tables are presented on the export and import of pork, there are clarifications on specific cooperating countries. Information is provided regarding rational investment in pig farming, its prospects; numbers that predict investment status.Ukraine has the material and technical grounds for the development of pig farming and maintaining a sufficiently high level of this industry in the country, even during martial law. It is even possible to develop a program of more profitable activities in this area. It is advisable to attract foreign investments for the organization of operation. We believe that it is necessary to develop a program, the goal of which will be the availability of pork for all segments of the population of Ukraine in the trade network. Undoubtedly, it is necessary to change the vector of international trade activity — to reduce the export of grain and increase the export of pork. Also, identify such an export niche that will ensure more efficient activity of pig farms.JEL Classification: А10, R11, R20